Treatment of lymphoid cells with the topoisomerase II poison etoposide leads to an increased juxtaposition of AML1 and ETO genes on the surface of nucleoli - Rubtsov, M.A.; Glukhov, S.I.; Allinne, J.; Pichugin, A.; Vassetzky, Y.S.; Razin, S.V.; Iarovaia, O.V. (Вiopolymers and Cell, 2011)
AML1 and ETO genes are known partners in the t(8,21) translocation associated with the treatment-related
leukaemias in the patients receiving chemotherapy with DNA-topoisomerase II (topo II) poisons. Aim. To
determine whether the genes AML1 and ETO are in close proximity either permanently or temporarily in the
nucleus. Methods. 3D FISH. Results. We found that in 5 % of untreated cells, alleles of AML1 and ETO are in
close proximity. This number increased two-fold in the cells treated with the topo II poison etoposide.
Surprisingly, in more than 50 % of the cases observed, co-localization of the genes occurred at the nucleoli
surface. We found also that the treatment of cells triggers preferential loading of RAD51 onto bcr of the AML1
and ETO genes. Conclusions. Our results suggest that the repair of DNA lesions introduced by topoisomerase II
poisons may be mediated simultaneously by multiple mechanisms, which may be the cause of mistakes resulting
in translocations.
Keywords: DNA-topoisomerase II, nucleoli, Rad51, AML1, ETO. Гени AML1 і ETO відомі як партнери по транслокації t(8,21)
асоційованої з розвитком вторинних лейкозів у пацієнтів, які піддавалися хіміотерапії із застосуванням інгібіторів топоізомерази II. Мета. Оцінити частоту взаємної колокалізаціїгенів AML1 і
ETO у культурі лімфоїдних клітин людини. Методи. 3D FISH. Результати. У 5 % необроблених клітин лінії Jurkat алелі AML1 і
ETO знаходяться в безпосередній близькості один від одного. У
клітинах, оброблених інгібітором топоізомерази II етопозитом,
частота подій колокалізації AML1 і ETO зростає в два рази. При
цьому більш ніж у 50 % випадків колокалізація генів відбувається
на поверхні ядерця. Показано, что обробка клітин етопозидом
спричиняє посилення зв’язування білка RAD 51 з кластерами точок розриву (bcr) генів AML1 і ETO. Висновки. Репарація розривів
ДНК, індукованих інгібіторами топоізомерази II, вірогідна за одночасної участі різних механізмів, що може бути причиною помилок, які викликають транслокації.
Ключові слова: ДНК-топоізомераза II, ядерця, Rad51, AML1,
ETO. Гены AML1 и ETO известны как партнеры по транслокации
t(8,21), которая ассоциирована с развитием вторичных лейкозов
у пациентов, подвергшихся химиотерапии с применением ингибиторов ДНК-топоизомеразы II. Цель. Оценить частоту взаимной
колокализации генов AML1 и ETO в культуре лимфоидных клеток
человека. Методы. 3D FISH. Результаты. В 5 % необработанных клеток линии Jurkat аллели AML1 и ETO находятся в непосредственной близости друг от друга. В клетках, обработанных ин -
гибитором ДНК-топоизомеразы II этопозидом, частота событий колокализации AML1 и ETO увеличивается в два раза. При
этом в более чем 50 % наблюдаемых случаев колокализация генов
происходит на поверхности ядрышка. Показано, что обработка
клеток этопозидом приводит к увеличению связывания белка
RAD 51 с кластерами точек разрыва (bcr) генов AML1 и ETO. Выводы. Репарация разрывов ДНК, индуцированных ингибиторами
ДНК-топоизомеразы II, вероятна при одновременном участии
различных механизмов, что может являться причиной ошибок,
приводящих к транслокациям.
Ключевые слова: ДНК-топоизомераза II, ядрышка, Rad51,
AML1, ETO.